A Study Of Women Micro Entrepreneurs In Malaysia: Livelihood Strategies And Challenges - Musa, Mazidah; Shuib, Rashidah; Selamat, Nor Hafizah; Mohd Isa, Salmi; Osman, Intan; Abu Bakar, Saridan (2016)
Micro entrepreneurs play an important role in Malaysia’s vision by achieving high income economy by 2020. Micro business assists local economies and contributes to a thriving economic growth. Government provides several types of aids and assistance such as microcredit facilities, short-term loan, tools and equipment to facilitate microbusinesses. As a result, by 2010, there were 77% micro entrepreneurs. However, according to the report by the Small and Medium Enterprise Corporation Malaysia (SME Corp. Malaysia), at least 75% of the business failed during their first year of operation. This figure is worrying and has to be studied in order to understand the real problems faced by Malaysian micro entrepreneurs. A qualitative study was conducted on a sample of 18 women micro entrepreneurs from Kedah, Perlis, Kelantan, Selangor and Penang using in-depth interviews. A set of guideline questions was constructed guided by the gender analytical framework and an adaptation of the Sustainable Livelihood framework, focusing on three aspects; financial capital, human capital and social capital as well as the livelihood strategies taken by the women. A thematic analysis done showed that the women entrepreneurs adopted several livelihood strategies such as doing innovation in business and producing various products to increase sales”. In terms of livelihood assets, the women entrepreneurs had to grapple with gender issues of child care, lack of family support and negative perceptions from the community, insufficient raw materials and capital to expand their businesses. Based on the research, sustainable livelihood has not been achieved by women entrepreneurs as a result of the problems mentioned. A multi-sectoral intervention are needed to support women entrepreneurs such as providing quality child care centers, provision of capital facilities and ensuring sufficient flow of raw materials.